Coaxial Dipole Array With Switching Transmit Sensitivities for Ultrahigh Field MRI - Bosch, Dario; Solomakha, Georgiy A.; Glang, Felix; Freudensprung, Martin; Avdievich, Nikolai; Scheffler, Klaus (Magnetic Resonance in Medicine, 2026)
Purpose: To investigate dipole antennas with electronically switchable transmit field patterns to improve flip angle homogeneity in ultra-high field MRI. Methods: Reconfigurable dipole elements that could produce two distinct electronically switchable (Formula presented.) field profiles were conceptualized and constructed. Eight such elements were combined into an array. Alteration of the field profiles was accomplished by modulating the currents along the dipoles using a combination of PIN diodes and lumped inductors. The behavior of these reconfigurable elements was studied in numerical electromagnetic simulations and 9.4T MRI measurements, investigating rapid switching of transmit sensitivities during excitation pulses in both single-channel and pTx mode operation. Results: For the simulated dipole elements, modulating the current densities along the dipole's axis causes a (Formula presented.) 30% change of the (Formula presented.) field between superior and inferior regions of the brain. When rapidly switched during excitation pulses, this degree of freedom can improve flip angle homogeneity, e.g., by a factor of (Formula presented.) 2.2 for a two kT points pTx pulse. For the constructed prototype array, the switching effect was observable but weaker, causing (Formula presented.) 10% superior-inferior (Formula presented.) variation. Conclusions: The proposed coaxial dipole array with switchable transmit sensitivities offers a novel degree of freedom for designing excitation pulses. The approach has the potential to improve flip angle homogeneity without necessitating an expensive increase in the number of independent transmit channels.
CRIS-Team Scopus Importer:2026-02-20
Keywords: arrays; dipoles; kT-points; pTx; RF-shimming